How Does Social Capital Work in Developing Karimunjawa Maritime Tourism? - Tri Marhaeni Pudji Astuti; Edi Kurniawan; Kuncoro Bayu Prasetyo; Atika Wijaya; Mohammad Syifauddin (Universitas Negeri Semarang, 2023)
This study intended to analyze how social capital works in the developing marine tourism in Karimunjawa Indonesia. This research was conducted in Karimunjawa. The data was collected with snowball sampling techniques. The data collection methods used consisted of participatory observation methods, in-depth interviews, and documentation. The data obtained were analyzed using the interactive analysis method. The results of the study indicate that the strong social capital formed in Karimunjawa has a very big influence on tourism activities in Karimunjawa. The social capital in tourism in Karimunjawa is based on many networks that are formed, supported by mutual trust, and still rooted in various social values and norms in the community that support the strength of existing social capital. It results in collective actions in the form of synergy and cooperation between the community and various tourism stakeholders in tourism activities in Karimunjawa. The social capital formed in Karimunjawa consists of three types. They are Bonding Social Capital, Social Bridging Capital, and Social Linking Capital which are complementary and mutually reinforcing so that they cannot be separated. However, between the three social capitals, bridging social capital is the biggest power base in realizing the progress of tourism in Karimunjawa.